Administrative Corruption and its Phenomenon Caused, and the Effects of the Consequences - Al Bakoush, Sadiq Miftah Mohammed; Saleh, Safinar (Journal of Economic, Administrative and Legal Sciences, 2018)
The study examined the issues of administrative corruption and the reasons for its emergence, and the resulting effects in Libya. Despite existence of such corruption, however, the Libyan people are resistanting against it, and to make sure that all forms and natures of the corruption never exits again, or at least to eliminate all manifestations of this corruption. The study indicates that there are reasons that led to the emergence of administrative corruption in Libya. Perhaps the political aspect is one of the most reasons for spreading of the phenomenon of administrative corruption in Libya, since the nature of the democratic practices and the rule of dictatorships and the prevalence of political tyranny contributed greatly to spreading of this phenomenon. The lack of an independent administrative judiciary to deal with administrative corruption cases has led to the unprecedented spreading of corruption, especially in the last century. This is due to the inability of the judiciary to deal with this type of lawsuits in administrative corruption. Additionally, the social reasons that are represented in the population structure of the society, which affects the ethics of loyalty and the coalition among its members, which affects the presence of the medium on it, because its existence for a long time, lead to the layers of social life in the Libyan societies, and has helped in this regard, as well as the absence of a unified administrative institutions.
Keywords: administrative; corruption; phenomenon; Libya